Awareness of Colorectal Cancer Risk Factors in Palestine: Where Do We Stand?. (13th June 2022) - Elshami, Mohamedraed; Dwikat, Mohammad F.; Al-Slaibi, Ibrahim; Alser, Mohammed; Mohamad, Balqees M.; Isleem, Wejdan S.; Shurrab, Adela; Yaghi, Bashar; Qabaja, Yahya Ayyash; Naji, Shoruq A.; Hmdan, Fatima K.; Ayyad, Mohammed M.; et al.
Abstract : PURPOSE: To assess the public awareness level of colorectal cancer (CRC) risk factors in Palestine and identify factors associated with the good awareness level. MATERIALS AND METHODS: Adult Palestinians were recruited using convenience sampling from hospitals, primary health care centers, and public locations in 11 governorates. The recognition of 11 CRC risk factors was evaluated using a translated-into-Arabic version of the validated bowel cancer awareness measure. Participants were given one point for each correctly recognized risk factor. The awareness level was determined by the number of CRC risk factors recognized: poor (0-3), fair (4-7), and good awareness (8-11). RESULTS: A total of 4, 877 participants, of 5, 254 approached, completed the questionnaire (response rate = 92.3%). The final analysis included 4, 623 questionnaires, 2, 700 from the West Bank and Jerusalem (WBJ) and 1, 923 from the Gaza Strip. Participants from the WBJ were older, gained higher monthly income, and had more chronic diseases than participants from the Gaza Strip. The most recognized modifiable CRC risk factor was not doing 30 minutes of moderate physical activity five times a week (n = 3, 846, 83.2%), whereas the least recognized was having a diet low in fiber (n = 1, 985, 42.9%). The most recognized nonmodifiable CRC risk factor was having a bowel disease (n = 3, 320, 71.8%), whereas the least recognized was having diabetes (n = 1, 581, 34.2%). Only 1, 840 participants (39.8%) demonstrated good awareness of CRC risk factors. Participants from the Gaza Strip were more likely than participants from the WBJ to have good awareness (46.5.0% v 35.0%). Female sex, knowing someone with cancer, and completing postsecondary education were all associated with good awareness. CONCLUSION: Awareness of CRC risk factors was found to be low in Palestine. There is a substantial need to raise awareness of CRC risk factors through educational campaigns and programs. Abstract : A national study in Palestine finds low awareness of colorectal cancer risk factors.